Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/1462-2920.15970
|View full text |Cite
|
Sign up to set email alerts
|

Under the canopy: disentangling the role of stemflow in shaping spatial patterns of soil microbial community structure underneath trees

Abstract: Summary Stemflow is a spatially concentrated input of rainwater at the base of trees, resulting from precipitation draining down tree branches to the stem. Depending on tree shape, stemflow can represent a significant fraction of the total rainfall that contacts the tree's canopy area, and can become chemically enriched along its drainage path. As a result, stemflow has been hypothesized to influence microbial communities in the receiving soil proximal to the stem. However, previous studies have (i) yielded co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…One potential pathway for the connection of the aboveground- and belowground habitats is stemflow ( Magyar et al, 2021 ). Rainwater, which runs down the branches and stems of trees carries a multitude of microorganisms, which are washed into the ground, and may become part of the soil microbiome ( van Stan et al, 2020 ; Magyar et al, 2021 ; Teachey et al, 2022 ). Conversely, fungal particles, such as spores, could be transported by wind in the other direction, from soil to bark, and adhere to bark surfaces and bark biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…One potential pathway for the connection of the aboveground- and belowground habitats is stemflow ( Magyar et al, 2021 ). Rainwater, which runs down the branches and stems of trees carries a multitude of microorganisms, which are washed into the ground, and may become part of the soil microbiome ( van Stan et al, 2020 ; Magyar et al, 2021 ; Teachey et al, 2022 ). Conversely, fungal particles, such as spores, could be transported by wind in the other direction, from soil to bark, and adhere to bark surfaces and bark biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Stemflow also acts as a link between the forest canopy and ground soil through the transport of animal remains, plant tissue, and other organic matter to the soil [21,22]. Stemflow has a considerable impact on the moisture conditions, physical and chemical properties, nutritional status, and microbial composition of the soil around the tree stem [23,24]. For example, stemflow leads to higher nutrient and water contents in the areas covered by a vegetation canopy compared to bare land, which is called the fertile island effect [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported changes in the community structure of soil fauna living near tree trunks, with some studies' emphasising stemflow's potential indirect effects on this near‐stem community by altering soil pH (Jóźwiak et al, 2013; Kaneko & Kofuji, 2000; Scheu & Poser, 1996). The only study to directly manipulate stemflow (removing it entirely from the near‐stem soils) found significant changes to soil bacterial community composition and its spatial variability (Teachey et al, 2022). However, the influence of stemflow metazoan transport on forest litter and soil remains an open question.…”
Section: Introductionmentioning
confidence: 99%